(untitled) (Physical Culture and Sport: Scientific Perspective, 2023)
The article analyzes the games of the best volleyball teams of the Ukrainian Championship in the 2022-2023 season. Total number of games (n=20). An expert evaluation of the results of the intervention of the head coach in the tactical actions of the team during time-outs (n=207) was given; effectiveness of player substitutions (n=438); use of video replays (n=171). The goal is to analyze the head coach’s ability to influence the tactical actions of the volleyball team during the competition. It has been established that the coach of a professional volleyball team corrects the tactical and technical actions of the players in the competition depending on the game situation and the actions of the opponent. The possibilities of the team’s head coach to influence the tactical actions of the team’s players are limited by the rules of the competition. He has the right to make substitutions of players, to take time outs and to demand video replays of disputed episodes of the game from the referees. By his actions, the head coach influences the pace of the game, the emotional and psychological setting of the players. It uses artificially created pauses in the game to provide tactical instructions and advice on the actions of the players in difficult sequences. The use of time-outs in professional volleyball is one of the most effective means of team management. During time-outs, the head coach corrects the tactical models of actions of the volleyball team players. More often, he focuses on changing the scheme of interaction between players, determining the features of the location of volleyball players during difficult innings of an opponent; bringing to the players the features of the organization of actions in defense and attack. It was found that 63.3% of the attention of the head coach of the volleyball team is focused on the organization of defense actions, 35.3% - on the effective completion of attacking actions. Player substitutions are most often made in order to change the tactical model of the team’s game and are carried out with the aim of: diversity of the team’s tactical actions; decision of individual game episodes in their favor; obtaining additional tactical pauses in the game. Video viewing of controversial episodes of the game are held in order to change the decision of the judges. It was found that 29.82% of video views have a positive decision. The use of the video replay system has a positive impact on the objectivity of refereeing decisions. During the preparation for the competition, the coach of the volleyball team builds several models of the team’s actions, which will allow solving the tournament tasks. Before the start of the competition, the head coach conducts an installation for the game, where he defines the basic model of the team’s collective actions and gives advice to each player. Depending on the game situation, the coach has the opportunity to use different models of the team’s tactical actions.